Prevalence of scabies and its associated environmental risk factors among the Forcibly Displaced Myanmar Nationals living in the Cox's Bazar district of Bangladesh - Md. Shakkor Rahman; A.B.M. Nahid Hasan; Ishrat Jahan; Azaz Bin Sharif (Elsevier, 2024)
Introduction: The Forcibly Displaced Myanmar Nationals (FDMNs) residing in refugee camps face various health challenges, including a rising prevalence of scabies, exacerbated by overcrowded conditions and limited healthcare access. This study aims to assess scabies prevalence, clinical features, and environmental factors among FDMNs, aiding interventions and recommendations for better health outcomes. Methodology: A cross-sectional study was conducted from April to May 2023 in six camps of Teknaf/Ukhia Cox's Bazar. Using a multistage sampling technique, 12 blocks were identified, and FDMNs seeking healthcare services from Primary Health Care posts were invited to participate in the study. Participants were adults, and children who volunteered to participate in this study. Scabies diagnosis was based on clinical examinations of exposed body areas by trained health professionals. Data on sociodemographic factors, environmental risk factors, and scabies symptoms were obtained through a semi-structured questionnaire administered by trained interviewers. Statistical analysis included descriptive statistics, Chi-square tests, and binary logistic regression models to explore associations between scabies infection and other explanatory factors. Result: A total of 679 FDMNs participated in the study, with a mean age of 29.13 years. Overall, 66.42 % of participants were diagnosed with scabies. Age, marital status, history of scabies infection, previous skin infection, family history of scabies and skin infection, floor type, pet animal, dust exposure, and seasonal exposure were significantly associated with the scabies infection. Binary logistic regression suggested that having history of scabies infection (OR 3.98, 95 % CI: 1.86 to 8.49, p < 0.001), skin infection (OR 2.46, 95 % CI: 1.32 to 4.58, p = 0.004), having family history of scabies infection (OR 3.06, 95 % CI: 1.29 to 7.23, p = 0.011), family history of skin infection (OR 27.41, 95% CI: 14.46 to 51.97, P < 0.001), having contact with street animal (OR 2.16, 95% CI: 1.27 to 3.66, P = 0.004), and winter season (OR 3.33, 95 % CI: 1.89 to 5.87, p < 0.001) were significantly associated with scabies infection. Conclusion: Tailored public health measures targeting hygiene, living conditions, and animal contact can mitigate the spread of scabies, particularly among vulnerable groups like Rohingya refugees, necessitating collaboration between stakeholders.